2021
DOI: 10.1155/2021/3502389
|View full text |Cite
|
Sign up to set email alerts
|

18F-PSMA-1007 PET in Biochemical Recurrent Prostate Cancer: An Updated Meta-Analysis

Abstract: Background. Prostate-specific membrane antigen- (PSMA-) targeted agents labeled with fluorine-18 (18F) have recently become available to evaluate patients with biochemical recurrent prostate cancer (BRPCa) by using positron emission tomography/computed tomography (PET/CT) or positron emission tomography/magnetic resonance imaging (PET/MRI). We performed a systematic review and meta-analysis about the detection rate (DR) of 18F-PSMA-1007 PET/CT or PET/MRI in BRPCa patients. Methods. A comprehensive computer lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…It has been reported that the detection rate (DR) of 18 F-PSMA-1007 PET/CT in local recurrence is related to PSA serum values. Results of the meta-analysis by Ferrari et al confirmed that 18 F-PSMA-1007 PET/CT demonstrated a good detection rate in biochemical recurrent prostate cancer (81.3%) and higher PSA values were associated with higher DR [ 38 ]. In addition, in a study by Lengana et al, the detection rate depending on the PSA level was determined.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the detection rate (DR) of 18 F-PSMA-1007 PET/CT in local recurrence is related to PSA serum values. Results of the meta-analysis by Ferrari et al confirmed that 18 F-PSMA-1007 PET/CT demonstrated a good detection rate in biochemical recurrent prostate cancer (81.3%) and higher PSA values were associated with higher DR [ 38 ]. In addition, in a study by Lengana et al, the detection rate depending on the PSA level was determined.…”
Section: Resultsmentioning
confidence: 99%
“…The main advantage of 18 F‐PSMA‐1007 is the possibility of large‐scale production in a cyclotron. Low excretion in urine compared to 68 Ga‐PSMA is theoretically advantageous but clinical superiority has not been established, possibly due to a higher number of unspecific findings (primarily in bone) (Awenat et al, 2021 ; Fendler et al, 2017 ; Ferrari & Treglia, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Its rapid blood clearance and high tumor-to-background ratios provide a high sensitivity and allow the detection of the smallest tumor lesions even in patients with low serum PSA levels. Furthermore, due to reduced urinary excretion of [ 18 F]PSMA-1007, local recurrence of PCa or regional lymph node metastases can be more accurately detected [ 3 , 4 , 21 24 ]. But also, benign findings are detected more often.…”
Section: Discussionmentioning
confidence: 99%
“…But also, benign findings are detected more often. Especially unspecific uptake in ganglia, in the ribs, or in unspecific lymph nodes should not be misinterpreted as metastases [ 8 , 21 ]. [ 18 F]PSMA-1007 can have a higher rate of tracer uptake in ganglia compared to [ 68 Ga]Ga-PSMA-11 [ 14 ].…”
Section: Discussionmentioning
confidence: 99%